Creativity of the discursive identity of the teacher - Пасинок, Валентина Григорівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2019)
The article discusses a creative discursive identity of the teacher as an expert in the center of any educational activity and source of knowledge which is given to students. Effectiveness of the teacher’s professional activity is mainly determined by the level of his skill in communication with other participants in educational process. With the help of creative pedagogical communication, social and professional experience is transmitted from the teacher to those who study; the same happens with specific characteristics associated with the objects under study and life in general. Such communication plays a leading role in shaping the personality of a young man, his self-awareness, life attitude and lifestyle. In the article, the teacher’s creativity is defined as an integral factor that constructs a discursive identity of the teacher. The paper also reviews innovative techniques for implementation the teacher’s creative component. It also analyzes the most effective ones: in the non-verbal sphere (kinetics, proxemics, paralinguistics, extralinguistics, takesics) and the verbal sphere (logical comprehension, detailing, concretization, dialogical style, trend detection).